DUGAAN GEJALA DEPRESI SILANG-DALAM DAN TINGKAT HOMOZIGOSITAS POPULASI KELAPA SAWIT HASIL PENYERBUKAN SENDIRI GENERASI KE-4 SP540T DAN GENERASI KE-5 DURA DELI - Rokhana Faizah; Sri Wening; Hernawan Yuli Rahmadi; Abdul Razak Purba (Pusat Penelitian Kelapa Sawit, 2016)
Inbreeding is a common method used to reproduce candidate mother plant from selected parental lines for commercial seeds in Reciprocal Recurrent Selection (RRS) oil palm breeding program. However this practice may increased homozigosity level of selected population. This study concerned the level of homozygosity of SP540T fourth generations and Dura Deli Dolok Sinumbah fifth generations (3 crosses respectively) and their correlation with inbreeding depression symptoms. Polymerase Chain Reaction-Simple Sequence Repeat (PCR-SSR) with 16 markers developed for oil palm was used to analyze 327 samples. The result shows that the levels of homozigosity of SP540T fourth selfing generation were ranged between 0.44-0.84 or 0.61 in average. While the levels of homozygosity of Dura Deli fifth selfing generations were ranged between 0.60-0.93 or 0.78 in average. The homozygosity level in Dura Deli was 1.27% higher than SP540T populations. Correlation analysis showed that the higher the level of homozygosity, the higher of the inbreeding symptoms 2 observed (R =0.95).